PRODUKSI PAKAN TERNAK DIMUSIM KEMARAU OLEH KELOMPOK TERNAK TANI SANGGAH BETES KABUPATEN ROTE NDAO - Foeh, Nancy Diana Frederika Katerina; Datta, Frans Umbu; Ndaong, Nemay Anggadewi; Detha, Annytha Ina Rohi (Universitas Nusa Cendana, 2024)
Community service is one of the programs that must be continued to be carried out in the community. In oder to reach the farmers needed in the Sanggah Betes Farmer group, Holoama Village, Lobalain District, Rote Ndao Regency, where the availability of fresh grass in the fields and tree leaves are abundant in February to May and Straw is also abundant in harvest season (rice straw and corn) as well as forage crops (grass odot) that introduced to Rote are also increasing. So the challenge is the utilization of this extraordinary potential food source is not optimal yet. The model of service activities offered to this group was in the form of socialization and direct practice of the service committee team to livestock groups under the local service supervision which is the Livestock Office of Rote Ndao Regency. The expected results of this service activity were this livestock group becomes a central example for other livestock groups and will continue to apply the knowledge that gained.